Grand Challenges in School Social Work: Collaboration and Constraint in School Social Workers' Sexuality Support for Children with Disabilities. Issue 1 (9th November 2017) - Bolin, Sharon J; Rueda, Heidi Adams; Linton, Kristen F
Abstract: Children with disabilities (CWD) face challenges to the development of their sexuality, in part due to a lack of appropriate, tailored sexual education in schools, role ambiguity regarding provision of sexual health services, and widespread discomfort with the topic. However, CWD have unique sexual health needs, an increased vulnerability to sexual and other forms of violence, and desire for skills and knowledge to build relationships. Using a phenomenological lens, authors conducted semistructured interviews with eight school social workers to understand how they are working with other professionals to support sexual and relational health of CWD (ages three to 11). Results indicate that school social workers collaborated with other professionals, although they also described multiple contexts in which other professionals had sole responsibility for sexual education and deferred to their expertise. Role ambiguity, policy restrictions, proscribed roles, and discomfort with the topic limited provision of needed services. Findings can assist school social workers seeking to build interdisciplinary collaboration, reduce role ambiguity, foster comfortable environments, and advocate for appropriate formats to support the sexual and relational health and well-being of CWD. They also suggest areas for policy change so that sexual support services are inclusive of all youths.